(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The present study is carried out to investigate the trade-off between liquidity and profitability. The main motive any business firm is to earn profit and for earning profit they need to manage their assets properly. The firm should be ready with its asset that are liquid to meet its short term i.e. current liabilities. Effective working capital management should be employed by the business firms to ensure trade-off between liquidity and profitability. The management of the business firm is naturally keen to measure its operating efficiency. Similarly the owners invest their funds in the expectation of reasonable returns. Sun Pharmaceutical Industries Ltd. is the fifth largest specialty generic pharmaceutical company in the world, which was incorporated in the year 1983. The Company has global presence with 41 manufacturing facilities across the world. India and the US are two predominant markets accounting for nearly 70% of the company’s revenue. The data was collected through secondary source i.e. audited financial statement for the 10 years from 2010-2011 to 2019- 20. The data analyzed by using several ratios related with liquidity and profitability, also used descriptive statistics, Correlation coefficient and liner multi regression analysis. The association of ROI, ROE and NPR with APP, CR and CA to TA is statistically significant and ROI, ROE and NPR are negatively correlated with ARP, ICP, CCC, CA to TA, GWCTR. Sun Pharmaceutical Industries Ltd. is taking benefit of extensive credit period allowed by their suppliers. However they should have stability in the decisions concerning management of current assets and liabilities.